Composition Engineering in Doctor‐Blading of Perovskite Solar Cells. Issue 18 (23rd May 2017) - Tang, Shi; Deng, Yehao; Zheng, Xiaopeng; Bai, Yang; Fang, Yanjun; Dong, Qingfeng; Wei, Haotong; Huang, Jinsong
Abstract : Organic–inorganic halide perovskite (OIHP) solar cells with efficiency over 18% power conversion efficiency (PCE) have been widely achieved with lab scale spin‐coating method which is however not scalable for the fabrication of large area solar panels. The PCEs of OIHP solar cells made by scalable deposition methods, such as doctor‐blading or slot‐die coating, have been lagging far behind than spin‐coated devices. In this study the authors report composition engineering in doctor‐bladed OIHP solar cells with p–i–n planar heterojunction structure to enhance their efficiency. Phase purer OIHP thin films are obtained by incorporating a small amount of cesium (Cs + ) and bromine (Br − ) ions into perovskite precursor solution, which also reduces the required film formation temperature. Pinhole free OIHP thin films with micrometer‐sized grains have been obtained assisted by a secondary grain growth with added methylammonium chloride into the precursor solution. The OIHP solar cells using these bladed thin films achieved PCEs over 19.0%, with the best stabilized PCE reaching 19.3%. This represents a significant step toward scalable manufacture of OIHP solar cells. Abstract : By tuning the composition of precursor solution high phase purity, perovskite thin films are obtained at a temperature of 120 °C via doctor‐blading, and over 19% power conversion efficiencies are achieved in inverted p–i–n structured perovskite solar cells.